Identifying Key Community Leaders to Assess Extension Programming Needs - Laura A. Warner; Sebastian Galindo-Gonzalez (EDIS, 2014)
Needs and assets assessments are a key task for Extension agents because they aid the development and delivery of research-based programs that address local needs. The purpose of this article is to describe the process of identifying key leaders to support an Extension agent’s needs assessment activities through interviews. This 4-page fact sheet was written by Laura A. (Sanagorski) Warner and Sebastian Galindo-Gonzalez, and published by the UF Department of Agricultural Education and Communication, May 2014.